Clinical features and viral kinetics in a rapidly cured patient with Ebola virus disease: a case report. Issue 9 (September 2015) - Schibler, Manuel; Vetter, Pauline; Cherpillod, Pascal; Petty, Tom J; Cordey, Samuel; Vieille, Gaël; Yerly, Sabine; Siegrist, Claire-Anne; Samii, Kaveh; Dayer, Julie-Anne; Docquier, Mylène; Zdobnov, Evgeny M; et al.
Summary: Background: A detailed description of viral kinetics, duration of virus shedding, and intraviral evolution in different body sites is warranted to understand Ebola virus pathogenesis. Patients with Ebola virus infections admitted to university hospitals provide a unique opportunity to do such in-depth virological investigations. We describe the clinical, biological, and virological follow-up of a case of Ebola virus disease. Methods: A 43-year-old medical doctor who contracted an Ebola virus infection in Sierra Leone on Nov 16, 2014 (day 1), was airlifted to Geneva University Hospitals, Geneva, Switzerland, on day 5 after disease onset. The patient received an experimental antiviral treatment of monoclonal antibodies (ZMAb) and favipiravir. We monitored daily viral load kinetics, estimated viral clearance, calculated the half-life of the virus in plasma, and analysed the viral genome via high-throughput sequencing, in addition to clinical and biological signs. Findings: The patient recovered rapidly, despite an initial high viral load (about 1 × 10 7 RNA copies per mL 24 h after onset of fever). We noted a two-phase viral decay. The virus half-life decreased from about 26 h to 9·5 h after the experimental antiviral treatment. Compared with a consensus sequence of June 18, 2014, the isolate that infected this patient displayed only five synonymous nucleotide substitutions on the full genome (4901A→C, 7837C→T, 8712A→G, 9947T→C, 16201T→C) despite 5 months of human-to-human transmission. Interpretation: This study emphasises the importance of virological investigations to fully understand the course of Ebola virus disease and adaptation of the virus. Whether the viral decay was caused by the effects of the immune response alone, an additional benefit from the antiviral treatment, or a combination of both is unclear. In-depth virological analysis and randomised controlled trials are needed before any conclusion on the potential effect of antiviral treatment can be drawn. Funding: Geneva University Hospitals, Swiss Office of Public Health, Swiss Agency for Development and Cooperation, and Swiss National Science Foundation.